Occupational profile, and alcohol and tobacco consumption in patients with head, neck, and lung cancer in the city Uberlândia, MG - Silveira Navarro, Vanessa; Borges de Araújo, Lúcio; Aparecida de Barros Junqueira, Marcelle (O Mundo da Saúde, 2020)
Cancer is the second leading cause of death in Brazil, and head, neck, and lung cancer are among the five most common types in the male Brazilian population. It is reported that tobacco, alcohol and occupational agents are important risk factors for the disease. This study aims to describe the work profile and the use of alcohol and tobacco among patients diagnosed with these types of cancers. It is a quantitative, descriptive, exploratory, transversal study. The sample consisted of 118 patients seen and registered at a public hospital, who answered a questionnaire that contained sociodemographic and professional information, in addition to the Fagerstrom Test and the AUDIT. Most participants were men, white, married, with an average age of 60, an incomplete primary education, income below one minimum wage, with the main occupational activities related to rural work, civil construction, and cleaning and maintenance. The history of alcohol and tobacco abuse, which also occurred after the diagnosis of cancer, was raised, as well as living with family members and co-workers who also used these substances. It is concluded that there is a need for assistance aimed at changing lifestyles during cancer treatment, expanding the vision of studies related to cancer for specific sociodemographic groups, concerning lifestyle and consumption habits, work profile, as well as work environment.